A systematic review of sarcopenia prevalence and associated factors in people living with human immunodeficiency virus - SeyedAhmad SeyedAlinaghi; Morteza Ghayomzadeh; Pegah Mirzapour; Seyed Farzad Maroufi; Zahra Pashaei; Zoha Ali; Marcarious M. Tantuoyir; Narjes Aghaie; Farzin Vahedi; Roghayeh Salmani; Mehrzad MohsseniPour; Kowsar Qaderi; et al. (Wiley, 2023)
Abstract People living with human immunodeficiency virus (HIV) (PLWH) appear to be at an increased risk of sarcopenia, which can have a devastating effect on their life due to consequences such as physical disability, poor quality of life, and finally death. This systematic review examined sarcopenia prevalence and its associated factors in PLWH. A systematic search was conducted using the keywords in the online databases including Scopus, PubMed, Web of Science, Embase and Cochrane databases from the dates of inception up to May 2022. The retrieved articles underwent a two‐step title/abstract and full‐text review process, and the eligible papers were selected and included in the qualitative synthesis. Data relating to the study population, purpose of study, gender, age, race, body mass index, medical history, paraclinical results and antiretroviral therapy as associated factors of sarcopenia were extracted. In addition, the prevalence of sarcopenia in PLWH and its promoting and reducing factors were also extracted. We reviewed the 14 related studies for identifying of sarcopenia prevalence and its associated factors in PLWH. The total number of PLWH in all the reviewed studies was 2592. There was no criterion for the minimum number of people with HIV and the lowest number of PLWH was 27, and the highest number was 860. Some studies reported a significantly higher prevalence of sarcopenia in HIV‐infected individuals compared with HIV‐negative controls as follows: 24.2-6.7%, 15-4% and 10-6%, respectively. We showed that, age (30-50 years), being female, >5 years post‐HIV diagnosis, multiple vertebral fractures, cocaine/heroin use and lower gamma‐glutamyl transferase level were the main promoting factors of sarcopenia. Higher educational level, employment, physical exercise, calf circumference >31 cm, and gait speed >0.8 m/s were also factors to reduce sarcopenia. Sarcopenia prevalence in PLWH is higher than HIV‐negative population. Given the importance and prevalence of sarcopenia among PLWH and its associated consequences (i.e., mortality and disability), determining its risk factors is of great importance.